Pesticidal Activity of Sundarban Mangrove Plant Extracts against Sitophilus Pests and Identification of Active Constituents Using LC-MS - Md. Abdur Rahman; Rinku Rani Paul; Chaina Biswas; Hakima Akter; Razina Rouf; Sushmita Nath; Jamil A. Shilpi; Lutfun Nahar; Stayajit D. Sarker; Shaikh Jamal Uddin (Advances in Pharmacological and Pharmaceutical Sciences)
Plants act as a rich source of novel natural pesticides. In the backdrop of the recent revival of interest in developing plant-based insecticides, this study was carried out to investigate the pesticidal activity of Sundarban mangrove plants. A total of nine different plant parts from five plants, namely, Aegiceras corniculatum, Excoecaria agallocha, Heritiera fomes, Xylocarpus moluccensis, and Xylocarpus granatum, were extracted with methanol and tested for insecticidal activity against two common stored product pests Sitophilus oryzae and Sitophilus zeamais using direct contact feeding deterrent wafer disc method. Three bark extracts from A. corniculatum, E. agallocha, and H. fomes showed potent and statistically significant insecticidal activity against both S. oryzae and S. zeamais pests (80–100% mortality). All the active bark extracts were further fractionated using C-18 solid-phase extraction (SPE) columns and tested for their insecticidal activity against S. oryzae pest to identify the active fraction. Only the SPE4 fraction (100% MeOH) from all the three active plants showed the activity against S. oryzae pest with a lethal concentration 50% (LC50) value of 0.5, 1.0, and 1.5 mg/disc for A. corniculatum, E. agallocha, and H. fomes, respectively. The active fraction of A. corniculatum was further profiled for identification of active compounds using LC-ESI-MS and identified (along with some unknown peaks) two previously reported compounds at m/z 625.17630 (isorhamnetin 3-O-rutinoside) and 422.25346 (paspaline) as major constituents. Insecticidal activities of these plants are reported in this study for the first time and would be useful in promoting research aiming for the development of new biopesticides from mangrove plants.